INFLUENCE OF ONE-WALL CARBON NANOTUBES ON THE DIELECTRIC PROPERTIES OF NEMATIC LIQUID CRYSTAL 6CHBT - Ковальчук, О.; Беженар, Ю.; Вовк, В.; Ксендзенко, А. (Science-based technologies, 2011)
Investigated was influence of the single-walled carbon nanotubes (NT) non-modified and modified with the group COOH with the concentration 0,02 wt.% on dielectric properties of nematic liquid crystal 6CHBT. It was shown that nanotubes decrease the conductivity value, so the modified NT decrease it almost twice more than non-modified ones. Presence of the same amount of magnetite in liquid crystal, like the NT, results in substantial (more than one order) increase of conductivity and parameters of near-electrode processes. This fact indicate that it is impossible to estimate the conductivity of multicomponent systems with different types of nanoparticles being basis on information about influence of each component owing to manifestation of collective effects.